Modeling the distribution of niche space and risk for a freeze‐tolerant ectotherm, Lithobates sylvaticus. Issue 7 (9th July 2019) - Fitzpatrick, Megan J.; Zuckerberg, Benjamin; Pauli, Jonathan N.; Kearney, Michael R.; Thompson, Kimberly L.; Werner, Lawrence C.; Porter, Warren P.
Abstract: Many animals depend on stable below‐the‐snow (subnivium) conditions to survive winter in seasonally cold regions. Freeze‐tolerant ectotherms may experience increased ice content and/or energy expenditure in suboptimal subnivium conditions, with implications for overwinter survival and body reserves available for spring reproduction. We used a novel mechanistic modeling approach to explore effects of winter climate on the microclimate conditions, energy expenditure, and ice dynamics of the freeze‐tolerant, subnivium‐dwelling wood frog ( Lithobates sylvaticus ) in the Upper Midwest and Great Lakes Basin region of the United States. We hypothesized that (1) frogs would experience the greatest energy cost to survive winter in southern regions of our study area, where air temperatures are warmer and shallower snow could allow for increased numbers of freeze–thaw cycles, and (2) frogs would be most vulnerable to lethal freezing in the cold, dry northwest portion of our study region. We found that total winter energy expenditure changed little with latitude because the effect of warmer soil temperatures (higher metabolic rates) to the south was offset by a shorter winter duration. Energy expenditures were greatest in the snowbelts of the Great Lakes, characterized by more persistent snow cover and relatively warm soil temperatures. In contrast, highest ice contents occurred in the northwest of the study region where air temperatures were coldest and snow was shallow. Thus, it appears that wood frogs experience a trade‐off between risk of lethal ice content and extensive use of body reserves across geographic space. Simulations showed that interpopulation differences in burrow depth and cryoprotectant concentration can influence risk of lethal ice content and overuse of body reserves prior to spring breeding, and those risks vary in relation to winter climate. Our mechanistic modeling approach is a novel tool for predicting risk and shifting niche space for cold‐adapted and subnivium‐dependent species.